PENGARUH WORD OF MOUTH TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA USAHA MIE AYAM PAK AGUS DI KOTA BATU - Yuda Oktavianto (Manajemen Bisnis, 2013)
Yuda OktaviantoPT. Surya MadistrindoE-mail: yudhaoktavianto@yahoo.comABSTRACTThe research objective was to determine the influence of communication Word Of Mouth (WOM) onconsumer purchasing decisions at Pak Agus chicken noodle products in Batu city. The method usedwas a survey. The dependent variable was purchase decision and the independent variable was Wordof Mouth Communication. Respondents were consumers who make repeat purchases in chicken noodlePak Agus least three times, as many as 100 people. Sampling technique used purposive sampling.Data collection was using questionnaires. Analysis tool used was a simple linear regression. Theresults showed the positive influential among variables Word Of Mouth (WOM) on Purchase Decisionwhich was supported by 77.2% contribution. It meant that all consumers who buy chickennoodle were 77.2% influenced by the communication word of mouth.Keywords: Communication, Word of Mouth, Purchase Decision